Interaction Rituals and Jumbled Emotions Among "Relative Strangers": Simulated Patient Work on a Trainee Complementary Therapy Practitioner Program. (9th July 2015) - Fixsen, Alison; Ridge, Damien; Kirkpatrick, Susan; Foot, Doug
Learning games such as role-play (which we refer to as "simulated interaction rituals") are commonly used as social tools to develop trainee health practitioners. However, the effect of such rituals on individual and group participant emotions has not been carefully studied. Using a heuristic approach, we explore the experiences of complementary therapy practitioner trainees (and their trainers) participating in a personal development course. Ten trainees and two tutors were interviewed, observational notes taken, and a secondary qualitative analysis undertaken. Participants and tutors described a medley of disparate emotional and moral responses to group rituals, conceptualized in this article as "jumbled emotions." Such emotions required disentangling, and both trainees and staff perceived participating in unfamiliar rituals "with relative strangers" as challenging. Front of stage effects are frequently processed "backstage, " as rituals threaten social embarrassment and confusion. Concerns around emotional triggers, authenticity, and outcomes of rituals arise at the time, yet trainees can find ways to work through these issues in time.